1998
DOI: 10.1159/000017087
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and Drug Use in Cognitively Impaired Elderly Living in Long-Term Care

Abstract: Cognitive impairment is associated with an increased mortality in older people. The prevalence and impact of comorbidity on functional status and mortality of demented patients has not been fully elucidated. Using a population-based data set, we describe the prevalence of cognitive impairment, functional status, principal comorbid conditions and 1-year survival for over 300,000 patients admitted to the nursing homes in five US states. Sixty-one percent of patients have some level of cognitive impairment, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 46 publications
5
18
1
1
Order By: Relevance
“…The inverse relationship between cognitive impairment and comorbidity confirms our previous results [7], and we show herein that it applies to different types of dementia. These results are in agreement with those of Hogan et al [25] who found that hypertension and body mass index decrease with increasing dementia severity in both AD and VaD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The inverse relationship between cognitive impairment and comorbidity confirms our previous results [7], and we show herein that it applies to different types of dementia. These results are in agreement with those of Hogan et al [25] who found that hypertension and body mass index decrease with increasing dementia severity in both AD and VaD.…”
Section: Discussionsupporting
confidence: 93%
“…We have documented that individuals with cognitive impairment are characterized by poor health status with a high prevalence of functional disability, and by a substantially increased mortality rate [7]. Surprisingly, we found that, compared to persons with normal cognitive Landi/Gambassi/Lapane/Sgadari/Mor/ Bernabei function, cognitively impaired patients had fewer comorbidities.…”
Section: Introductioncontrasting
confidence: 54%
“…8 14 26 Similarly, non-vascular comorbid conditions were associated with mortality in some studies,6 7 but not in others 914 21These different results may be attributable to an underrepresentation of comorbid conditions among demented patients 4857 In agreement with the results of other authors,7 9 14sensory impairment affecting vision and hearing was associated with a slightly increased risk of mortality in our study.…”
Section: Discussionsupporting
confidence: 89%
“…This finding might be explained by the association of delirium with dementia, which Morichi et al: Delirium in Nursing Homes www.karger.com/dem © 2018S. Karger AG, Basel DOI: 10.1159 might be associated with a high risk of underrecognition and undertreatment of somatic diseases [37]. On the other hand, the negative association between polypharmacy and delirium might be explained by an appropriate deprescription in subjects with dementia and severe disability, who are more often delirious.…”
Section: Discussionmentioning
confidence: 99%